Correction: Micropatterning neuronal networks. Issue 11 (4th May 2016) - Hardelauf‡, Heike; Waide‡, Sarah; Sisnaiske, Julia; Jacob, Peter; Hausherr, Vanessa; Schöbel, Nicole; Janasek, Dirk; van Thriel, Christoph; West, Jonathan
Abstract : Correction for 'Micropatterning neuronal networks' by Heike Hardelauf, et al., Analyst, 2014, 139, 3256–3264.